Pengelolaan Media Sosial Instagram @Persib Sebagai Bentuk Implementasi Kegiatan Cyber Public Relations - Fadillah, Aldi; Rosyidi, Imron; Astuti, Dyah Rahmi (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2023)
As time went by, the @Persib Instagram account gradually began to promote various activities by designing interesting and informative content, with the aim of building trust from the public. This research aims to describe how Persib Bandung manages the @Persib Instagram account in Cyber Public Relations activities through the concept of The Circular Model Of Some. The method used in this research is a descriptive method with a qualitative approach. The research results regarding the management of Instagram @Persib social media as a form of implementation of cyber public relations activities have stages, namely: 1) Share, 2) Optimize, 3) Manage and, 4) Engage. So managing social media Instagram @Persib as a form of implementing cyber public relations activities can be a reference in implementing digital public relations management on social media.